COVID-19: Third dose booster vaccine effectiveness against breakthrough coronavirus infection, hospitalisations and death in patients with cancer: A population-based study. (November 2022) - Lee, Lennard Y.W.; Ionescu, Maria C.; Starkey, Thomas; Little, Martin; Tilby, Michael; Tripathy, Arvind R.; Mckenzie, Hayley S.; Al-Hajji, Youssra; Appanna, Nathan; Barnard, Matthew; Benny, Liza; Burnett, Alexander; et al.
Abstract: Purpose: People living with cancer and haematological malignancies are at an increased risk of hospitalisation and death following infection with acute respiratory syndrome coronavirus 2. Coronavirus third dose vaccine boosters are proposed to boost waning immune responses in immunocompromised individuals and increase coronavirus protection; however, their effectiveness has not yet been systematically evaluated. Methods: This study is a population-scale real-world evaluation of the United Kingdom's third dose vaccine booster programme for cancer patients from 8th December 2020 to 7th December 2021. The cancer cohort comprises individuals from Public Health England's national cancer dataset, excluding individuals less than 18 years. A test-negative case-control design was used to assess the third dose booster vaccine effectiveness. Multivariable logistic regression models were fitted to compare risk in the cancer cohort relative to the general population. Results: The cancer cohort comprised of 2, 258, 553 tests from 361, 098 individuals. Third dose boosters were evaluated by reference to 87, 039, 743 polymerase chain reaction coronavirus tests. Vaccine effectiveness against breakthrough infections, symptomatic infections, coronavirus hospitalisation and death in cancer patients were 59.1%, 62.8%, 80.5% and 94.5%, respectively. Lower vaccine effectiveness was associated with a cancer diagnosis within 12 months, lymphoma, recent systemic anti-cancer therapy (SACT) or radiotherapy. Patients with lymphoma had low levels of protection from symptomatic disease. In spite of third dose boosters, following multivariable adjustment, individuals with cancer remain at an increased risk of coronavirus hospitalisation and death compared to the population control (OR 3.38, 3.01, respectively. p < 0.001 for both). Conclusions: Third dose boosters are effective for most individuals with cancer, increasing protection from coronavirus. However, their effectiveness is heterogenous and lower than the general population. Many patients with cancer will remain at the increased risk of coronavirus infections even after 3 doses. In the case of patients with lymphoma, there is a particularly strong disparity of vaccine effectiveness against breakthrough infection and severe disease. Breakthrough infections will disrupt cancer care and treatment with potentially adverse consequences on survival outcomes. The data support the role of vaccine boosters in preventing severe disease, and further pharmacological intervention to prevent transmission and aid viral clearance to limit the disruption of cancer care as the delivery of care continues to evolve during the coronavirus pandemic. Highlights: Largest population evaluation of third dose SARS-CoV-2 disease (COVID-19) vaccination in patients with cancer. Vaccine effectiveness against COVID-19 infections, hospitalisation and death assessed. Lower vaccine effectiveness associated with recent systemic anti-cancer therapy. Patients with lymphoma had low levels of vaccine protection from symptomatic COVID-19. Patients with cancer remain at a higher risk of severe COVID-19 hospitalisation and death.